2021
DOI: 10.3389/fvets.2021.746755
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mastitis Pathogens and Antimicrobial Susceptibility of Isolates From Cattle and Buffaloes in Northwest of Pakistan

Abstract: Mastitis is the most prevalent disease of dairy animals, imparting huge economic losses to the dairy industry. There is always a dire need to monitor the prevalence of mastitis, its bacteriology, and evaluation of antimicrobial susceptibilities for mastitis control and prevention. Therefore, the objectives of this study were to investigate: (i) the prevalence of mastitis in cattle and buffaloes; (ii) identification of bacteria associated with mastitis; (iii) antimicrobial susceptibility of bacterial isolates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
29
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 18 publications
(37 reference statements)
8
29
3
1
Order By: Relevance
“…Thus, CM was highest in cows in comparison to buffaloes however SCM was highest in buffaloes. Mustafa et al (2011) and our recent study (Ali et al, 2021) also reported higher prevalence of CM in cows than in buffaloes. It has been reported that buffaloes are generally more resilient to different diseases such as bovine mastitis due to their strong immune system (Pal and Chakravarty, 2020).…”
Section: Antimicrobial Resistance and Susceptibility Of Bacterial Pat...supporting
confidence: 58%
See 3 more Smart Citations
“…Thus, CM was highest in cows in comparison to buffaloes however SCM was highest in buffaloes. Mustafa et al (2011) and our recent study (Ali et al, 2021) also reported higher prevalence of CM in cows than in buffaloes. It has been reported that buffaloes are generally more resilient to different diseases such as bovine mastitis due to their strong immune system (Pal and Chakravarty, 2020).…”
Section: Antimicrobial Resistance and Susceptibility Of Bacterial Pat...supporting
confidence: 58%
“…A total of 541 samples from mastitic animals were further cultured to identify the bacterial pathogens. The identification of bacterial isolates was carried out up to the level of genus as described earlier (Ali et al, 2021). In addition, antimicrobial resistance and susceptibility profiling of the isolated bacteria from mastitic cattle and buffaloes was carried out on Muller-Hinton agar (Oxoid TM , Thermo Scientific Inc. USA).…”
Section: Bacteriology and Antimicrobial Resistance Profiling Of Masti...mentioning
confidence: 99%
See 2 more Smart Citations
“…The changes that we identified in the present study on water buffalo are sensibly different from bovine milk, being limited to 72 lipids species that are differentially abundant in the NAS-IMI affected milk. Although water buffaloes are regarded as less subjected to mastitis, this concept is debatable, as mastitis is the most prevalent disease in this species, in both farming conditions where animals are kept in an intensive dairy milk productive system 22 , or where the hygienic environment is suboptimal 51 . Still, at least for what concerns the specific NAS-IMI and the lipidome content, the water buffalo seems much less sensitive to dairy cows, given that our results showed that NAS-IMI induced limited changes in the lipid profile of affected quarter milk.…”
Section: Discussionmentioning
confidence: 99%